2020
DOI: 10.1002/ceat.202000286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphene Oxide Nanosheets and Al2O3Nanoparticles on CO2Uptake in Semi‐clathrate Hydrates

Abstract: Gas hydrate/clathrate hydrate formation is an innovative method to trap CO2 into hydrate cages under appropriate thermodynamic and/or kinetic conditions. Due to their excellent surface properties, nanoparticles can be utilized as hydrate kinetic promoters. Here, the kinetics of the CO2 + tetra‐n‐butyl ammonium bromide (TBAB) semi‐clathrate hydrates system in the presence of two distinct nanofluid suspensions containing graphene oxide (GO) nanosheets and Al2O3 nanoparticles is evaluated. The results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The reason for this is the reduction in the number of nucleation sites over time, which results in a reduction in the rate of gas consumption. On the other hand, the driving force decreases over time [25]. According to the results, it is observed that there is a high correlation between the experimental results and the firstorder kinetic model.…”
Section: Kinetic Modelmentioning
confidence: 67%
See 2 more Smart Citations
“…The reason for this is the reduction in the number of nucleation sites over time, which results in a reduction in the rate of gas consumption. On the other hand, the driving force decreases over time [25]. According to the results, it is observed that there is a high correlation between the experimental results and the firstorder kinetic model.…”
Section: Kinetic Modelmentioning
confidence: 67%
“…In the other work, the effect of aluminum oxide and NGO in the presence of surfactant on the formation kinetics of carbon dioxide hydrate was tested. The results showed that the concentration of 400 ppm NGO and 0.4 wt% Al2O3 had the most significant impact on the kinetics parameter of CO2 hydrate formation [25]. Zhou et al [26] also showed that gas consumption, induction time, and the ratio of water to hydrate conversion were affected by the simultaneous presence of tetra-n-butyl ammonium bromide (TBAB) and graphite nanoparticles (GN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, thanks to the substantially important steps in nanomaterial science and technology, it is possible to apply multifunctional nanomaterials in wide prospective application areas, including sensors, optics, , fluid dynamics, , heat-transfer applications, electronics, energy, hydrogen production and storage, , catalysis, water decontamination, , environmental applications, biotechnology, etc. Because of their remarkable electrical conductivity, thermal characteristics, and catalytic qualities, carbon and Mxene-based two-dimensional (2D) nanomaterials have attracted a lot of attention from contemporary researchers among the diverse forms of nanostructures. Graphene, which is a well-known 2D material has generated great interest in various fields, such as material science, physics, biology, and chemistry. As a result, the promising properties of graphene, including high electrical conductivity, high surface area, high thermal conductivity, high optical transmittance, and high mechanical properties, promote these materials for potential applications in diverse applications. Furthermore, reduced graphene oxide (rGO) is derivative of graphene oxide (GO); it is fabricated by the reduction of GO .…”
Section: Introductionmentioning
confidence: 99%
“…In this current era of the modern world, nanomaterials are being used in each and every field of science and technology including environmental remediation , and protection, biotechnology, sensors/electrochemical sensors, heat transfer , and fluid dynamics applications, optics, , electronics, food safety, energy storage and conversion systems, , hydrogen production and storage technologies, catalysts, etc. Among the variety of nanomaterials, metal nanoparticles (NPs) and their hybrid composites are gaining popularity in many applications.…”
Section: Introductionmentioning
confidence: 99%